2013
DOI: 10.1002/sia.5300
|View full text |Cite
|
Sign up to set email alerts
|

Differential capacity and chronocoulometry studies of a quaternary ammonium surfactant adsorbed on Au(111)

Abstract: The adsorption of a model quaternary ammonium surfactant, octyltrimethylammonium triflate, on Au(111) has been studied using capacity and chronoculometry methods. The surfactant adsorbs on the metal surface as a non-dissociated ion pair at moderate potentials but can be desorbed by either positive or negative polarization. Within the adsorption region, two states are observed which correspond to a horizontal monolayer and a higher coverage vertically oriented film. Measurements of capacity transients upon pote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…Measurements of the surface reactivity as a function of crystal orientation and the concentration of adsorbate can test this hypothesis and offer a deep understanding of the facet-dependent chemistry that causes anisotropic growth of 1D metal nanostructures. To this end, single-crystal electrochemical measurements have been demonstrated as a powerful analytical tool for obtaining such information in the fields of electrocatalysts, electrochemical deposition, , and corrosion. To date, single-crystal electrochemistry has been used to test the hypothesis of capping agent for AuNR and CuNW growth. There remain many additional nanostructure syntheses in which single-crystal electrochemistry can be applied to provide a deeper understanding of the facet-selective chemistry.…”
Section: Investigation Of the Growth Mechanismmentioning
confidence: 99%
See 1 more Smart Citation
“…Measurements of the surface reactivity as a function of crystal orientation and the concentration of adsorbate can test this hypothesis and offer a deep understanding of the facet-dependent chemistry that causes anisotropic growth of 1D metal nanostructures. To this end, single-crystal electrochemical measurements have been demonstrated as a powerful analytical tool for obtaining such information in the fields of electrocatalysts, electrochemical deposition, , and corrosion. To date, single-crystal electrochemistry has been used to test the hypothesis of capping agent for AuNR and CuNW growth. There remain many additional nanostructure syntheses in which single-crystal electrochemistry can be applied to provide a deeper understanding of the facet-selective chemistry.…”
Section: Investigation Of the Growth Mechanismmentioning
confidence: 99%
“…Notable examples include in situ TEM, ,,, dark-field optical microscopy (DFOM), , and transmission X-ray microscopy (TXM). All these techniques have been used to observe the growth of 1D metal nanostructures in real time, quantify their growth kinetics, and distinguish between atomic addition and oriented attachment. In addition, single-crystal electrochemistry has provided new insights into the roles played by halides and capping agents during anisotropic growth. Computational simulations have also been used to evaluate different hypotheses pertaining to how anisotropic growth occurs, offering additional insights into atomic-level processes that determine the rates of anisotropic growth, as well as why anisotropic growth occurs. ,, This section focuses on the contributions made by these new analytical methods, each of which can contribute a different perspective on the development and testing of models to account for 1D growth.…”
Section: Investigation Of the Growth Mechanismmentioning
confidence: 99%
“…In addition to attachment, atomic addition is another common route of nanocrystal growth. As discussed in section , the rate of atomic addition to a specific type of facet can be regulated using surface capping agent, resulting in the formation of nanocrystals enclosed by that facet. , To this end, experimental measurements such as electrochemical methods have been conducted to test which species are responsible for the facet-dependent growth. However, it is still unclear why the actions of these species are facet selective. Many researchers have also endeavored to investigate the role of capping agent in the asymmetrical growth and symmetry breaking of Ag, Au, and Pd nanocrystals. , In the case of Au nanorods, different from the previously proposed bilayer model, molecular dynamics simulations suggested that CTAB was distributed as cylindrical micelles on the Au surface .…”
Section: Summary and Outlookmentioning
confidence: 99%